Elong sagala of ma’bakkang ritual i Gattareng Matinggi: semiotic riview of Rifaterre - Nurfandiati Nurfandiati; Azis Azis; Suarni Syam Saguni (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2021)
Elong sagala of ma’bakkang ritual i Gattareng Matinggi: semiotic riview of Rifaterre. Thesis of Regional Language and Literature Department, Makassar State University. The data in this study is the elong sagala text contained in the ma'bakkang ritual in Gattareng Matinggi village using Riffaterre's semiotic theory based on heuristic and hermeneutic reading as a scalpel to find out the meaning of language and literary conventions. This research is qualitative. This study uses data analysis techniques, namely data collection, data reduction, data presentation, and then drawing conclusions. The object of this research is the elong sagala text of ma'bakkang ritual in Gattareng Matinggi village which is analyzed based on the heuristic and hermeneutic readings of Riffaterre's semiotic theory. The results of the analysis based on heuristic readings found that elong sagala text data was not linguistically structured, there were words that did not have a literal meaning, used many repetitions in each stanza, and used a lot of metaphors. Then the meaning based on Elong sagala hermeneutic reading, namely based on the literary convention of the elong sagala text, it was found that the Gattareng Matinggi community lived side by side with Islamic religious beliefs and adhered to animism. Then the elong text describes a situation filled with suffering, fear, anxiety, and hope. Based on the results of the analysis of the text of elong sagala revealed that elong sagala is a spell to prevent smallpox. A disease that usually affects children.